Solusi Sosial atas Kontestasi Agama Mayoritas-Minoritas di Arjawinangun Cirebon, Indonesia - M. Yusuf Wibisono; Akhsin Ridho; Ahmad Sarbini; Dadang Kahmad (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to see that the existence of minority religions in Arjawinangun is very much considered part of the life of the majority religion. The majority religion's protection is intensely felt by minority religions as a form of religious tolerance and highly appreciates differences to become the primary capital of economic, social, and religious development in their communities. This study examines society's sacred theology, the approach, and the method used in social change. This type of field research uses descriptive qualitative analysis. The study results can be argued that: Religious plurality is the basis for people's attitudes to accept and respect other religions. The community has a moderate attitude towards the existence of religious anti-pluralism and pro-pluralism groups. The conclusion is that religious pluralism becomes a means to the common good in solving humanitarian and national problems. Based on the modern, pluralistic social considerations with its religious typology, it is the theology of religious freedom due to charismatic pluralist religious figures' influence.